Adherence to oral anticoagulation therapy - Lana Lekic (Journal of Health Sciences, 2014)
Introduction: Warfarin is the most frequently prescribed anticoagulant. Clinical treatment is demanding because of the narrow therapeutic range and considerable differences between the patients. The aim of this survey is to establish adherence to warfarin in subjects who have been prescribed warfarin as a long-term therapy.